2021
DOI: 10.1093/nop/npab021
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, cognition, and COVID: delivering direct-to-home teleneuropsychology services to neuro-oncology patients

Abstract: Background The COVID-19 pandemic induced rapid adoption of telemedicine services for neuro-oncology patients at an increased risk of infection. Neuropsychological assessment is important to neuro-oncology care yet challenging to complete outside of a structured testing environment. Teleneuropsychology (TNP) has been explored in limited populations and proven feasible and reliable. Conducting TNP visits directly to patients' home (DTH) had minimal prior study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 61 , 62 , 63 , 64 To our knowledge, there have not yet been published studies examining the reliability and validity of teleneuropsychology in breast cancer, but its feasibility and acceptability have been demonstrated in other cancer populations. 65 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 61 , 62 , 63 , 64 To our knowledge, there have not yet been published studies examining the reliability and validity of teleneuropsychology in breast cancer, but its feasibility and acceptability have been demonstrated in other cancer populations. 65 …”
Section: Discussionmentioning
confidence: 99%
“…However, there is research supporting the equivalency of in‐person and remote cognitive testing and the use of teleneuropsychology during the pandemic has been accepted as a reliable and valid alternative to in‐person assessment 61–64 . To our knowledge, there have not yet been published studies examining the reliability and validity of teleneuropsychology in breast cancer, but its feasibility and acceptability have been demonstrated in other cancer populations 65 …”
Section: Discussionmentioning
confidence: 99%
“…The validity of in-home TeleNP testing has also been examined indicating that telehealth scores do not differ significantly from in-person testing, which further supports the use of our current testing model [ 26 , 27 ]. A study conducted by Gardner and colleagues, was the first to demonstrate acceptability and feasibility of direct to home TeleNP in a neuro-oncology clinical sample [ 28 ]. This study demonstrated that TeleNP is a feasible practice, while also recognizing limitations in assessing motor and executive functioning.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The demonstrable success of telemedicine across multiple fields of neurosurgery has validated its continued use over the last 24 months. Telemedicine applications were successful in teleneuropsychology, telestroke, and tele-ICU rounding [ 4 6 ]. For example, our center’s retrospective cohort study determined that telemedicine led to a faster diagnosis of stroke, more frequent administration of tPA, and better long-term outcomes [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%